2008
DOI: 10.1042/cs20070382
|View full text |Cite
|
Sign up to set email alerts
|

Circulating vascular endothelial growth factor and systemic inflammatory markers in patients with stable and exacerbated chronic obstructive pulmonary disease

Abstract: The aim of the present study was to assess circulating levels of VEGF (vascular endothelial growth factor), a biomarker with prognostic significance in cardiovascular disease, and markers of systemic inflammation in patients with stable and exacerbated COPD (chronic obstructive pulmonary disease). Lung function parameters, arterial blood gas analysis and circulating levels of VEGF, IL-6 (interleukin-6), TNF-alpha (tumour necrosis factor-alpha), CRP (C-reactive protein), fibrinogen and the peripheral blood neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
41
2
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 40 publications
9
41
2
3
Order By: Relevance
“…In previous studies only the up-regulation of blood levels of VEGF has been reported during the acute exacerbation of COPD (Valipour et al 2008). Our research group has confirmed elevated concentrations of VEGF in the airways of patients with COPD, but we have not found any additional elevation of angiogenic factors at the time of exacerbation of COPD (Kristan et al 2012).…”
Section: Biomarkers Of Angiogenesissupporting
confidence: 67%
“…In previous studies only the up-regulation of blood levels of VEGF has been reported during the acute exacerbation of COPD (Valipour et al 2008). Our research group has confirmed elevated concentrations of VEGF in the airways of patients with COPD, but we have not found any additional elevation of angiogenic factors at the time of exacerbation of COPD (Kristan et al 2012).…”
Section: Biomarkers Of Angiogenesissupporting
confidence: 67%
“…VEGF synthesis is increased by prostacyclin in human lung fibroblasts in vitro [51] and this cross talk may be important during inflammation and hypoxic conditions in the distal lung promoting angiogenesis in areas with poor circulation and ventilation. It has been shown that patients with acute exacerbations present high levels of VEGF in the circulation compared to stable COPD patients and healthy individuals [128]. In a small study with bronchial biopsies, patients without glucocorticosteroid treatment showed more bronchial vascularisation, larger vessels and more VEGF receptors expressed in the tissue compared to COPD patients that were treated with inhaled glucocorticosteroids [119].…”
Section: Vascular Changes and Growth Factors In Copdmentioning
confidence: 99%
“…Studies have shown that VEGF is increased in pulmonary arteries and plasma of COPD patients, in parallel with prominent vascular remodelling and decreased PB EPCs (52,65 (67).…”
Section: Mobilization and Migration Of Epcs In Copdmentioning
confidence: 99%